Potensi Keanekaragaman Hayati, Iklim Mikro dan Serapan Karbon pada Ruang Terbuka Hijau Kampus Mendalo Universitas Jambi (Biodiversity Potential, Micro Climate and Carbon Uptake at The Green Area of Jambi University Campus at Mendalo) - . Nursanti; Elly Indra Swari (Bioplantae, 2013)
This research purpose is to evaluate the potential of biological diversity, micro climate and carbon uptake at the green area of Jambi University Campus. It’s used purposive random sampling. The result showed that there are 34 type of trees with various diameter. Among the trees there are Dalbergia latifolia, Fagraea fragrans and Palaguium gutta, which is classified to be protected. The green area of Jambi University Campus especially at green strip could decrased the temperature about 2.00 C.Key Words: Carbon, green area, biodiversity.